(untitled) - Thompson, Arthur A. (New York, 2007)
The book is particularly suited for courses where the instructor wishes to provide students with a foundation in the core concepts and analytical tools of strategic management and an introduction to the literature of strategic management.
Keywords: Strategic planning,Business planning,Lập kế hoạch chiến lược